Waste Polystyrene‐derived Sulfonated Fluorescent Carbon Nanoparticles for Cation Sensing. Issue 36 (21st September 2022) - Teo, Jerald Y. Q.; Zheng, Xin Ting; Seng, Debbie Hwee Leng; Hui, Hui Kim; Chee, Pei Lin; Su, Xiaodi; Loh, Xian Jun; Lim, Jason Y. C.
Abstract: Polystyrene, one of the most widely‐produced plastics worldwide, is non‐biodegradable and has unsustainable life‐cycles with only a small fraction recycled presently. Hence, there is considerable effort underway to explore new methods to give post‐consumer polystyrene waste a new lease‐of‐life as functional materials. In this study, we report the synthesis of the first polyanionic fluorescent carbon nanoparticles from sulfonated waste polystyrene food containers via an environmentally‐benign route in water. By virtue of their sulfonate groups, these biocompatible and fluorescent nanoparticles show a number of distinct behaviours in the presence of different main group and transition metal cations. Al 3+ brings about both fluorescence enhancement and nanoparticle precipitation, whilst fluorescence quenching was observed for paramagnetic and toxic transition metal cations, with Cu 2+ eliciting the most sensitive fluorescence response (LoD=26 μM). These fluorescence intensity perturbations are likely a consequence of direct metal cation coordination to the exposed sulfonate groups on the nanoparticles. Our findings suggest the potential of using post‐synthetically modified waste plastics to produce a family of luminescent carbon materials for environmental sensing of these hazardous cations. Abstract : Waste polystyrene is upcycled into water‐soluble, biocompatible polyanionic fluorescent carbon nanoparticles, which show broad‐spectrum fluorescence sensing behavior towards a range of toxic heavy metal cations for potential environmental monitoring applications. Al 3+ and transition metal cations are found to elicit distinct sensory responses.